Microbial-Derived Uremic Toxins: Role in the Pathogenesis of Comorbidities in Patients with Chronic Kidney Disease - M. O. Pyatchenkov; A. A. Vlasov; E. V. Sherbakov; S. P. Salikova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2023)
Аim: to analyze the significance of microbial-derived uremic toxins (MDUT) in the pathogenesis of comorbidities in patients with chronic kidney disease (CKD).Key findings. Increased excretion of nitrogen metabolism products into the intestines of patients with CKD is associated with uremic dysbiosis; changes in the metabolic activity of the gut microbiota and the leaky gut syndrome; which largely cause the accumulation of MDUT in the internal environment of the body: indoxyl sulfate; p-cresyl sulfate; trimethylamine-N-oxide; etc. The results of recent studies allow to consider these metabolites as an independent risk factor for adverse outcomes in people with CKD due to the progression of renal dysfunction to the terminal stage; as well as frequent cardiovascular; neurological; bone mineral; nutritional and other complications.Conclusion. MDUT are one of the key modulators of the pathogenetic relationship between the gut and kidneys. Therapeutic manipulations with intestinal microbiota can be considered a promising strategy for preventing complications associated with uremia.